Mixed convection in fluid superposed porous layers - Dixon, John M. (Springer, 2017)
This Brief describes and analyzes flow and heat transport over a liquid-saturated porous bed. The porous bed is saturated by a liquid layer and heating takes place from a section of the bottom. The effect on flow patterns of heating from the bottom is shown by calculation, and when the heating is sufficiently strong, the flow is affected through the porous and upper liquid layers. Measurements of the heat transfer rate from the heated section confirm calculations. General heat transfer laws are developed for varying porous bed depths for applications to process industry needs, environmental sciences, and materials processing. Addressing a topic of considerable interest to the research community, the brief features an up-to-date literature review of mixed convection energy transport in fluid superposed porous layers.
Keywords: Heat -- Convection.; Heat -- Transmission.; Porous materials -- Thermal properties.; elektronické knihy; electronic books